(untitled) (Bangladesh Journal of Medical Science, 2020)
Introduction: Seeking help when needed is an integral part of the learning process. How effectively the students seek help when they experience academic difficulties can influence their success in the University. Academic help-seeking is an useful strategy that promotes effective learning and benefits the students in academic excellence. The present study aimed to assess the attitude on academic help seeking behavior among nursing students. Methods: The study was conducted among 96 first year B.Sc. Nursing students of a selected nursing college. The samples were selected by using non probability purposive sampling technique. A self administered three point likert scale on attitude on academic help seeking was used to collect the data. The data was analyzed by descriptive and inferential statistics. Result: The item wise responses show that 82% of the students said sometimes they clarify the doubts with the teacher when they don’t understand the class, whereas 75% responded that they always ask with their friends. Majority refers in the library (93%) and search in the website (94%).Students responded to some factors which hinders them to seek help. With regard to the approach ability of teachers,17% always felt that the teachers are neither approachable nor friendly to seek help whereas, 45% felt sometimes felt, in addition to that 25% sometimes felt they don’t approach the teachers because they give importance only to the best students. Sixteen percent always felt that they were not given opportunity to express their academic problems. The overall results revealed that majority (59%) of the students had favorable attitude towards academic help seeking whereas 41% had neutral attitude and none of them had unfavorable attitude. It shows that the students have positive attitude to seek help for the academic problems. Conclusion: The overall result shows that the students have favorable attitude towards academic help seeking. The factors influencing them not to seek help should be considered and as academician we must provide exemplary academic support for the success of every student. Academic help-seeking is an useful strategy that promotes effective learning and benefits the students in academic excellence. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.717-721